The international certification of Authorized Economic Operator - AEO - La Noire Núñez, José Antonio (2022)
Through this article, the authors intend to share their comments with the reader about the criteria of the Authorized Economic Operator — AEO) Program, as well as its benefits. Next, we will review the conditions, requirements and international standards in terms of security established by the World Customs Organization — WCO that would allow companies engaged in foreign trade to secure their international logistics chain and make Customs Clearances increasingly easy, more agile and economical.